Green wireless local area network received signal strength dimensionality reduction and indoor localization based on fingerprint algorithm. (30th August 2013) - Ma, Lin; Zhou, Caifa; Qin, Danyang; Xu, Yubin
SUMMARY Green wireless local area network (WLAN) is an emerging technology to achieve both the purposes of power conservation and high‐speed accessing to the Internet because of the working on‐demand strategy adoption and high density access points (APs) deployment. Although it is good news to data traffic service, Green WLAN brings severe challenges to the indoor localization service based on fingerprint algorithm. Redundant APs will greatly enlarge the radio map and introduce a much heavier computation burden to the terminal for localization in the online phase. In addition, APs in Green WLAN are powered on and off to make balances between data traffic service demand and energy saving goals so that the received signal strength (RSS) sampled online and recorded in the radio map offline are rarely matched in the same detected AP number, which leads to asymmetric matching problem occurring in the fingerprint algorithm. In this paper, we propose to make a nonlinear dimensionality reduction on the RSS by local discriminant embedding algorithm to realize both the computation burden decreasing and asymmetric matching problem resolving for the fingerprint algorithm in Green WLAN. The simulation results show that our proposed methods could effectively reduce the computation burden in the online phase and make the fingerprint algorithm operate more robustly when the RSS is reduced to the intrinsic dimensionality in Green WLAN. Copyright © 2013 John Wiley & Sons, Ltd.